(untitled) (Journal of Pathology of Nepal, 2020)
Background: Regardless of the type of diabetes mellitus, there is always a Beta-cell dysfunction leading to absolute insulin deficiency in type 1 diabetes mellitus or associated with insulin resistance in case of type 2 diabetes mellitus. Materials and Methods: A total of 267 subjects consisting of 164 diabetic patients and 103 non-diabetic apparently healthy individuals were analysed. The plasma insulin and c-peptides levels were determined using enzyme link immunosorbent assay, while plasma glucose level was determined using standard spectrophotometric method. Results: The biochemical results showed that the mean plasma glucose of Type 1 diabetes (213.65±20.35) and Type 2 diabetes (218.78+7.85) were significantly (P<0.05) higher than that of non-diabetic control (81.88±17.22) mg/dl; the mean plasma glucose and the systolic reading of the Diabetes Mellitus with Nephropathy, hypertension, coronary artery disease, neuropathy, and retinopathy patients were significantly (p<0.05) higher than the control subjects. Among diabetic hypertensive patients mean insulin and c-peptide levels were significantly (p<0.05) lower, while the mean insulin level was insignificantly (p>0.05) lower in diabetic patients with neuropathy or coronary artery disease. No significant (p>0.05) differences was observed in the mean plasma c-peptide level, and diastolic reading of diabetic patient with neuropathy. There were no significant (p>0.05) differences in the mean plasma c-peptide level, systolic and diastolic readings of Diabetic patients with coronary heart disease or retinopathy. Conclusion: There were significant differences in the blood pressure parameters in both the diabetes mellitus and diabetic complications in this study.